PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH PADA BANKALTIMTARA CABANG TENGGARONG - Intan agus Riyani (University of Widya Gama Mahakam Samarinda, 2019)
Intan Agus Riyani, the influence of Service Quality on Customer Loyalty through customer satisfaction at Bankaltimtara Tenggarong Branch, With Advisor I Dr. Novel Reonald, S. Pt., M.M and Mrs. Dian Irma Aprianti, S.IP., M.M.The purpose of this study is to determine and analyze whether Tangible (X1), Reliability (X2), Ressponsivvenes (X3), Assurance (X4) and Empathy (X5) variables, have a partial and simultaneous influence on customer satisfaction and customer loyalty of Bankaltimtara Tenggarong branches, To find out and analyze whether the customer satisfaction variable has a positive and significant effect on customer loyalty at the Tengalong Bankaltimtara branch.This research method is quantitative descriptive using statistical analysis tools with the help of the SPSS computer program version 22.0. to find out the influence and relationship of each variable.From the analysis, it is known that the tangible variables (X1), Reliability (X2), Assurance (X4) have a positive but not significant effect on customer satisfaction because tcount <ttable, Ressponsivvenes (X3) are negative and not significant to customer satisfaction tcount -0.444 < table 1.66, and Empathy (X5) shows a positive and significant value to customer satisfaction tcount 3,413> 1.66.From the results of the analysis, it is known that Tangible, Reliability, Ressponsivvenes, Assurance and Empathy have a positive positive effect simultaneously on customer satisfaction and on customer loyalty of Bankaltimtara Tenggarong Branch.From the results of the analysis, it is known that the variable customer satisfaction (Y1) has a positive and significant effect on customer loyalty (Y2) Bankaltimarawa Tenggarong branch t arithmetic> T table is 3,229> 1.66.From the analysis, it is known that tangible variables, Reliability, Ressponsivvenes have a positive but not significant effect on customer loyalty, tcount 0.79 <ttable, Assurance has a negative effect on customer loyalty thitung -0,626 <ttable 1.66 and Empathy shows positive and significant values of satisfaction Customers thitung 1.972> 1.66 table.From the results of the F test (simultaneous) the results of the F test of all X variables towards greater satisfaction, which means that in this study customer loyalty is created due to a sense of satisfactionKeywords: Service Quality, Customer Satisfaction, Customer Loyalty.